PECKING ORDER THEORY TEST ON THE CAPITAL STRUCTURE OF INSURANCE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) - Isti Fadah; Sekarini Arum Sejati; Ariwan Joko Nusbantor; Istatuk Budy Yuswanto (Journal of Management and Business, 2018)
This study aims to analyze the effect of profitability, asset structure, and business risk on the capital structure of insurance companies listed in Indonesia Stock Exchange (BEI) in 2012- 2016 and to know the pattern of financing pecking order theory applied to insurance companies listed in the Stock Exchange Indonesia (BEI) for 2012-2016. This research is explanatory research. The population in this study are all insurance companies listed on the Indonesia Stock Exchange (BEI) in 2012-2016 amounting to 12 companies and samples used in this study as many as 10 companies. The analysis method used is multiple linear regression analysis with t test. The results showed that profitability does not affect the capital structure of insurance companies, asset structure and business risk significantly influence the capital structure of insurance companies listed on the Indonesia Stock Exchange (BEI) in 2012-2016. While on pecking order theory testing, there are 3 (three) insurance companies that tend to follow the pecking order theory financing pattern and 7 (seven) companies do not follow the pecking order theory financing pattern.